Piperlongumine and some of its analogs inhibit selectively the human immunoproteasome over the constitutive proteasome - Bosc, Elodie; Nastri, Jhennifer [UNESP]; Lefort, Valérie; Valli, Marilia [UNESP]; Contiguiba, Fernando; Pioli, Renan; Furlan, Maysa [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; El Amri, Chahrazade; Reboud-Ravaux, Michèle (Elsevier, 2018)
The natural small molecule piperlongumine A is toxic selectively to cancer cells in vitro and in vivo. This toxicity has been correlated with cancer cell ROS, DNA damage and apoptotic cell death increases. We demonstrate here a new mechanistic property of piperlongumine: it inhibits selectively human immunoproteasome with no noticeable inhibition of human constitutive proteasome. This result suggests that immunoproteasome inhibition, a mechanism independent of ROS elevation, may also partly play a role in the anticancer effects observed with piperlongumine. Structure-activity relationships of piperlongumine analogs suggest that the lactam (piperidonic) ring of piperlongumine A may be replaced by the linear olefin –NHCO-CH2=CH2 to improve both in vitro inhibitory efficiency against immunoproteasome and cellular toxicity.
Keywords: Immunoproteasome; Piperlogumine; Piperlongumine analogs; Proteasome